French Revolution: Murder scenes in the Church of Baarfüsser to Avignon: 16 Oct. 1791 - Unknown:::Creator::::::::::::
Plate no. 37 of a set of engravings of the French Revolution: Murder scenes in the Church of Baarfüsser to Avignon: 16 Oct. 1791